Morphotropic phase boundary in the BFO-BTO solid solutions: role of synthesis conditions. Issue 1 (22nd June 2022) - Abramov, A. S.; Safina, V. A.; Alikin, D. O.; Karpinsky, D. V.; Zhaludkevich, D. V.; Pryakhina, V. I.; Kiselev, E. A.; Shut, V. N.; Zhaludkevich, A. L.; Shur, V. Ya.; Kholkin, A. L.
Abstract: The morphotropic phase boundary (MPB) region of the BFO-BTO solid solution is studied by comprehensive macroscopic and local methods, focusing on the synthesis conditions that influence the final phase composition and functional response. The difference between the phase distribution and local switching behavior in two sets of the BFO-BTO solid solutions prepared with different applied pressures is revealed and attributed to the local chemical inhomogeneity forming due to certain differences in the solid-state sintering reactions. More homogeneous mixing of the polar and non-polar phases stimulates the non-polar-to-polar phase transition and widening the MPB region.